2018
DOI: 10.1002/ajb2.1055
|View full text |Cite
|
Sign up to set email alerts
|

The role of cold cues at different life stages on germination and flowering phenology

Abstract: In general, cold is more important for seed germination in annuals and plants from environments with warm temperatures and variable precipitation. In contrast, cold is more important for flowering in perennials: it accelerates flowering in plants from lower precipitation environments, and it increases flowering proportion in plants from cooler, more stable precipitation environments. We discuss our findings in the context of the variable environments plants experience within a population and the variation enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…However, the optimal response to temperature cues may vary with climate among populations. Although clinal within‐species variation in dormancy and germination traits is often reported (Montesinos‐Navarro et al., ; Vidigal et al., ; Barga et al., ; Fernández‐Pascual et al., ; Hernández et al., ; López et al., ), fewer studies have examined intraspecific variation in seed chilling responses, particularly across climatic gradients (Cavieres and Arroyo, ; Debieu et al., ; Rubin and Friedman, ). Our results demonstrate extensive variation in stratification (chilling) requirements and ambient temperature responses in S. tortuosus populations across elevation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal response to temperature cues may vary with climate among populations. Although clinal within‐species variation in dormancy and germination traits is often reported (Montesinos‐Navarro et al., ; Vidigal et al., ; Barga et al., ; Fernández‐Pascual et al., ; Hernández et al., ; López et al., ), fewer studies have examined intraspecific variation in seed chilling responses, particularly across climatic gradients (Cavieres and Arroyo, ; Debieu et al., ; Rubin and Friedman, ). Our results demonstrate extensive variation in stratification (chilling) requirements and ambient temperature responses in S. tortuosus populations across elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Annual populations reproduce exclusively via seeds, by which plants make showy bee‐pollinated flowers that can each contain hundreds of ovules that develop into seeds. Previous research on 23 populations of M. guttatus demonstrated that germination occurs with or without stratification and suggests that both annuals and perennials can germinate in either the fall or spring (Rubin & Friedman, ). For this study, we used a single annual population (SKZ) located near Skutz Falls in Cowichan River Provincial Park, Vancouver Island, British Columbia, Canada (48°46′955″N, 123°57′173″W).…”
Section: Methodsmentioning
confidence: 99%
“…Similar variation in life cycle has been demonstrated in Arabidopsis thaliana , mostly segregating between populations, but there is also some evidence for polymorphic strategies within populations (Kronholm et al ., ; Montesinos‐Navarro et al ., ; Burghardt et al ., ). However, unlike A. thaliana , there is no clear geographic pattern associated with dormancy in M. guttatus (Rubin & Friedman, ), suggesting that small‐scale environmental heterogeneity might be important in maintaining strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The Mimulus guttatus species complex (section Simiolus, DC, Phrymaceae) comprises about a dozen closely related species that inhabit a broad altitudinal range across the Pacific Northwest and exhibit substantial variation in life-history [31]. Considerable effort has been made to characterize lifehistory in this group, particularly within or between annual species [15,23,[32][33][34][35][36], and between annuals and perennials [5,24,[37][38][39][40][41][42][43][44][45][46]. Little is known about life-history divergence among perennials in this group, although they account for a sizable fraction of species and inhabit ecologically unique habitat relative to annuals.…”
Section: Introductionmentioning
confidence: 99%